COMMON GRAMMATICAL ERRORS FOUND IN STUDENTS’ WRITING - Ma, Fransiskus B; Doi, Maksimilianus; Liru, Marianus W (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2022)
This study aimed at exploring the types of common grammatical errors are found in the students’ writing and finding out the dominant type of common grammatical errors found in students’ writing. This study used descriptive qualitative and quantitative method. The data were taken from the 21 compositions of students who took Basic Writing Class in English Letter Study Program, Faculty of Language and Literature of Flores University. Each writing has three kinds of writing. They are about family member, individual favorite object, and natural objects descriptions. The upshots of the study indicates there are 9,1% students who made errors in verb tense, 12,6% students who made errors in subject-verb agreement, 15,3% students made error in article, 4,5% students made error in preposition, 6,3% students made error in number, 4,5% students made error in pronoun, 1,8% students made error in possessive, 1,8% students made in word choice, 11,7% students made error in spelling, 19,8% students made error in word order, 7,2% students made error in capitalization, and 5,4% students made error in punctuation. The errors are caused from many factors; the students are still confused to choose the right word in a sentence because of the lack of knowledge or poor vocabularies and its use. Besides, errors happened because of their first language (Indonesian logical thinking), or we could say the learners’ mother tongue interference (interlingua source), some students tried to translate the words one by one from Indonesian language into English without paying attention to the English structure rules.